PENINGKATAN HASIL BELAJAR PENGURANGAN BILANGAN CACAH DENGAN PENDEKATAN MATEMATIKA REALISTIK DI KELAS II SD NEGERI - Herlina, Feni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The purpose of this study was to describe the improvement of student learning outcomes in learning civics Realistic Matematic Education in class II SDN 18 V Koto Timur Padang pariaman. The research was conducted at SDN 18 V Koto Timur with research subjects were students of class II which amounts to 10 people. RPP cycle assessment results I obtained an average of 77% with both criteria, the second cycle 82% with criteria very well. Aspects of teacher appraisal cycle I gained an average of 76% with both criteria and second cycle 81% obtained with the criteria very well. Student learning outcomes in cycle I gained an average of 69% with sufficient criteria and second cycle 79% with both criteria.   Kata kunci: hasil belajar,Pengurangan bilangan cacah, PMR